Presencia de Munidopsis robusta en el Caribe colombiano (A. Milne Edwards, 1880) (Crustacea: Anomura: Munidopsidae) - Ortega-Echeverría, Candelaria; Universidad de Cartagena (2013)
The first record of M. robusta in Colombia is presented. The specimens were collected by demersal trawling at 500 m depth in front of the departments of La Guajira and Bolívar using a semi-ballon net. Collected specimens were washed onboard with seawater and preserved in 95 % ethanol. The characteristics of the water column were measured with a multi-parameter CTDO instrument. Sediments were collected using a Box-corer and a granulometric analysis was performed. A species diagnosis is presented together with comments regarding its distribution and bathymetric and geographic ranges. With this new record, the number of Colombian species of Munidopsis increases to 23. Moreover, the distribution of this species for the Caribbean is extended.